2018
DOI: 10.1111/jvh.12903
|View full text |Cite
|
Sign up to set email alerts
|

Serum hepatitis B surface antigen correlates with fibrosis and necroinflammation: A multicentre perspective in China

Abstract: The kinetics of serum hepatitis B surface antigen (HBsAg) during the natural history of hepatitis B virus (HBV) infection has been studied, but the factors affecting them remain unclear. We aimed to investigate the factors affecting HBsAg titres, using data from multicentre, large-sized clinical trials in China. The baseline data of 1795 patients in 3 multicentre trials were studied, and the patients were classified into 3 groups: hepatitis B early antigen (HBeAg)-positive chronic HBV infection (n = 588), HBeA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
3
12
0
Order By: Relevance
“…Some studies have investigated the correlation of serum HBsAg and HBV DNA with liver pathological grades and stages in patients with chronic HBV infection [31][32][33][34][35][36]. e results of this study were basically consistent with those studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Some studies have investigated the correlation of serum HBsAg and HBV DNA with liver pathological grades and stages in patients with chronic HBV infection [31][32][33][34][35][36]. e results of this study were basically consistent with those studies.…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have shown that serum HBsAg of HBeAg-positive patients and serum HBV DNA of HBeAgnegative patients are valuable but not very satisfactory in predicting liver inflammation intensities and fibrosis levels [31][32][33][34][35][36]. Lately, preliminary studies have demonstrated that anti-HBc may be useful in predicting liver inflammation intensities and fibrosis levels [15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…HBsAg and HBeAg were roughly parallel to HBV DNA quantities in the absence of drug and virus mutations (12)(13)(14)(15). It was recognized that HBsAg can predict CHB progression and can be used to monitor antiviral efficacy in chronic HBV infected patients (16)(17)(18)(19). In our results, there were significant differences between the Minimal grade and Non-minimal grades (mild, moderate) group in age, ALT, AST, serum HBsAg, HBeAg, and HBV DNA quantitation by analysis of factors associated with liver inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the HPCV could affect viral replication and the level of serum HBV DNA levels and HBsAg titers is not well clear. Therefore, it is necessary to Current studies indicated that the expression of HBV DNA and HBsAg is declined in CHB patients with hepatic fibrosis (8,9). However, the previous study showed that the decrease in HBV DNA level from liver fibrosis stage from 1 to 4 is not a true reflection of a decline of viral replication level in hepatic parenchyma cells.…”
Section: Statistical Analysis Of Serum Hbv Dna/hbsag Serum Hbv Dna/hbsag Apportioned By the Same Hpcv In Different Inflammation Gradesmentioning
confidence: 97%
“…The more accumulation of inflammation and fibrosis caused by a viral infection, the less hepatic parenchyma cell volume (HPCV) can be provided to HBV replication (4,5). In clinical practice, the replication of HBV is usually assessed by viral DNA load and HBV surface antigen (HBsAg) in serum (6,7), and the decline of these two clinical parameters was often observed in CHB patients with hepatic fibrosis in different degree (8,9). However, the dynamic changes of serum HBV DNA and HBsAg levels in different liver inflammation grades are not well clear.…”
Section: Introductionmentioning
confidence: 99%